Design of 3D Hybrid Plant Extract/Marine and Bovine Collagen Matrixes as Potential Dermal Scaffolds for Skin Wound Healing - Aida Lahmar; Maroua Rjab; Fairouz Sioud; Mouna Selmi; Abir Salek; Soumaya Kilani-Jaziri; Leila Chekir Ghedira (The Scientific World Journal)
Tissue engineering involves the use of smart biomimetic hybrid matrices to reinforce the cellular interaction with the matrix and restore native properties after regeneration. In this study, we highlight the potential of 3D collagen sponges soaked with bioactive extract, to enhance the wound healing process in vivo. Acid-soluble collagen from two sources, marine and bovine, were extracted and characterized physiochemically using Fourier transform infrared spectroscopy (FTIR) and SDS-PAGE. Our results confirmed that the extracted collagens were mainly composed of collagen type I with slight molecular structure differences. Both collagens present two different α chains (α1 and α2) and one β chain. Highly interconnected 3D scaffolds from collagen from the skin are designed and added by the widely known healing plants Pistacia lentiscus and Calendula officinalis. The resulting 3D collagen matrices possess fine biocompatibility with skin cells, Hacat (keratinocytes), and 3T3-L1 (fibroblasts) cells. To evaluate the potential wound healing effect, a collagen sponge soaked with the bioactive extract was tested on BALB/c mice. Our findings confirmed that sponges significantly improve animal re-epithelialization by increasing wound closure. Consequently, spongy collagen scaffolds loaded with Pistacia lentiscus and Calendula officinalis could be used as potential wound dressing material.